Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1440-1711.2000.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulating immune responses with probiotic bacteria

Abstract: It has been known for years that commensal bacteria in our intestines play an important role metabolizing digesta in the lumen and in so doing provide an additional source of nutrients. The composition of commensal bacteria is highly stable and characteristic for an individual over time but does appear to vary considerably between individuals.1 Dietary changes, stress and consumption of antibiotics can disturb the balance of commensal bacteria and a healthy balance can be reestablished with probiotic supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
156
1
17

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(186 citation statements)
references
References 20 publications
(22 reference statements)
8
156
1
17
Order By: Relevance
“…Indeed, it has already been shown that probiotics may lead to an increased IgA production [59] and stimulation of macrophage and NK activity [15,46]. Moreover, several studies have reported that probiotics are able to regulate both anti-and pro-infammatory cytokine production.…”
Section: Immunomodulationmentioning
confidence: 99%
“…Indeed, it has already been shown that probiotics may lead to an increased IgA production [59] and stimulation of macrophage and NK activity [15,46]. Moreover, several studies have reported that probiotics are able to regulate both anti-and pro-infammatory cytokine production.…”
Section: Immunomodulationmentioning
confidence: 99%
“…Em populações pediátricas, o efeito de agentes probióticos parece ser muito significante contra diarréias virais (rotavírus), sugerindo que um mecanismo imunológico seja responsá-vel pelos efeitos benéficos 33 . Já foi também verificado que a administração oral de Lactobacillus casei Shirota (LcS) aumenta a imunidade inata, estimulando a atividade de células Natural Killer 5 .…”
Section: Microorganismos / Gruposunclassified
“…Dentre os benefícios apontados, citam-se o antagonismo aos agentes patogênicos, o efeito de barreira da microbiota e a modulação das funções imunes 2,[4][5][6] .…”
unclassified
See 2 more Smart Citations